20. YÜZYILDA İNGİLTERE'NİN ORTADOĞU'DAKİ EKONOMİ POLİTİKASI: IRAK ÖRNEĞİ - GEZE, AYSUN (Fırat Üniveristesi, 2024)
İngiltere'nin Ortadoğu coğrafyasındaki politikalarını anlamak için, öncelikle Osmanlı Devleti ile ilişkilerine bakmak önemlidir. Bu dönemde bu coğrafya Osmanlı Devleti'ne aitti. İki devlet arasındaki resmi ilişkiler, 16. yüzyılda ilk İngiliz elçisinin İstanbul'a gelmesiyle başladı. Başlangıçta Osmanlı-İngiliz ilişkileri, İngiltere'nin imtiyazlar elde etmesiyle dostluk ilişkileri şeklinde devam etti. Ancak zamanla değişen görüşler nedeniyle iki devlet arasındaki dostluk sona erdi ve 1875'ten itibaren çatışmaya dönüştü. Bu süreçte etkili olan birçok faktör vardı, ancak güç dengelerindeki değişiklikler ve çıkar ilişkileri en önemlileriydi. İngiltere, Sanayi Devrimi ile büyük güç haline gelerek dünya siyasetinde söz sahibi oldu ve Ortadoğu'ya girmeye başladı. Günümüzde hala önemini koruyan Ortadoğu bölgesi, tarihi kimliği, dini önemi, coğrafi konumu, siyasi ve ekonomik açıdan önemli bir yapıya sahiptir. Dolayısıyla bölgeye sahip olmak isteyen birçok unsur ve politika, geçmişten günümüze devam etti. İngiltere bu coğrafyada kendi çıkarları için birçok bölgede faaliyetlerini sürdürdü. Başlangıçta sömürgelerini korumak amacıyla politikalar yürütülürken, zamanla coğrafyanın sunduğu zenginlikler ve petrolün varlığı, bölgeyi daha da cazip hale getirdi. Özellikle Irak'ta birçok idari ve ekonomik politika uygulandı. Irak'ın ekonomik, politik, stratejik ve siyasi önemi bu noktada öne çıktı. Çalışmanın ilk bölümünde Osmanlı-İngiliz ilişkileri ve bu süreçteki olaylar anlatıldı. İkinci bölümünde Ortadoğu coğrafyasına ve İngiltere'nin Ortadoğu'daki tarihsel sürecine değinildi. Üçüncü bölümde ise konu Irak özelinde ele alınarak Irak bölgesi ve İngiltere'nin bölgedeki idari ve ekonomik politikalarına yer verildi. Anahtar Kelimeler: Osmanlı Devleti, İngiltere, Ekonomi, Ticaret, Ortadoğu, Irak, Petrol, İngiliz politikaları

To understand England's policies in the Middle East, it is important to first look at its relations with the Ottoman Empire. During this period, this geography belonged to the Ottoman Empire. Official relations between the two states began in the 16th century, when the first British ambassador came to Istanbul. In the beginning, Ottoman-British relations continued as friendly relations, with England gaining privileges. However, due to changing views over time, the friendship between the two states ended and turned into conflict from 1875 onwards. There were many factors effective in this process, but changes in the balance of power and relations of interest were the most important. England became a great power with the Industrial Revolution, had a say in world politics and began to enter the Middle East. The Middle East region, which still maintains its importance today, has an important structure in terms of its historical identity, religious importance, geographical location, and political and economic structure. Therefore, many elements and policies that want to own the region have continued from the past to the present. England continued its activities in many regions in this geography for its own interests. While policies were initially carried out to protect the colonies, over time the riches offered by the geography and the existence of oil made the region even more attractive. Many administrative and economic policies were implemented, especially in Iraq. Iraq's economic, political, strategic and political importance came to the fore at this point. In the first part of the study, Ottoman-British relations and the events in this process were explained. In the second part, the geography of the Middle East and the historical process of England in the Middle East were touched upon. In the third chapter, the issue was discussed specifically in Iraq and the administrative and economic policies of the Iraqi region and England in the region were included. It was aimed to contribute to the literature with this study, Key Words: Ottoman Empire, England, Economy, Trade, Middle East, Iraq, Oil, British policies
Britain's economic policy in the Middle East in the 20th century: The Iraq example
Keywords: Ekonomi